2021
DOI: 10.1126/sciadv.abi9643
|View full text |Cite
|
Sign up to set email alerts
|

The tempo of Ediacaran evolution

Abstract: New radio-isotopic data bracket the age of late Ediacaran fossil assemblages and two negative carbon isotope excursions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 103 publications
4
82
0
Order By: Relevance
“…S1 for a high-resolution version of this figure . whilst present and radiometrically calibrated in South China, is expressed most completely and with highest resolution in multiple sections by carbonates of the Dabis Formation in both the Zaris and Witputs sub-basins of the Nama Group. This is a recently recognized distinct negative δ 13 Ccarb excursion (Yang et al, 2021), herein termed the basal Nama excursion (BANE, Fig. 1b).…”
Section: Fig 1 Sequence Stratigraphic and Carbon Isotope Chemostratig...mentioning
confidence: 86%
See 3 more Smart Citations
“…S1 for a high-resolution version of this figure . whilst present and radiometrically calibrated in South China, is expressed most completely and with highest resolution in multiple sections by carbonates of the Dabis Formation in both the Zaris and Witputs sub-basins of the Nama Group. This is a recently recognized distinct negative δ 13 Ccarb excursion (Yang et al, 2021), herein termed the basal Nama excursion (BANE, Fig. 1b).…”
Section: Fig 1 Sequence Stratigraphic and Carbon Isotope Chemostratig...mentioning
confidence: 86%
“…To date, efforts to produce a global composite Ediacaran δ 13 Ccarb record (e.g. Macdonald et al, 2013;Yang et al, 2021) have revealed the middle Ediacaran Shuram negative anomaly at around <579 ->564 Ma (Rooney et al, 2020;Yang et al, 2021), followed by a positive shift from ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A time interval between c. 635 Ma and 550 Ma was constrained for the depositional age of the Doushantuo Formation exposed at the Jiulongwan and Jijiawan sections by means of thermal ionization mass spectrometry (TIMS) U-Pb dating of zircon grains from two interbedded tuff beds around the basal Doushantuo Formation and near the Doushantuo-Dengying Formation boundary (Condon et al 2005;Yang et al 2021;Fig. 1c).…”
Section: Geological Setting and Sampling Informationmentioning
confidence: 99%